Determinants of sovereign bond yield spreads in the EMU: an optimal currency area perspective - Constantini, M. (2015)
In the light of the recent financial crisis, we take a panel cointegration approach that allows for structural breaks to the analysis of the determinants of sovereign bond yield spreads in nine economies of the European Monetary Union. We find evidence for a level break in the cointegrating relationship. Moreover, results show that (i) fiscal imbalances - namely expected government debt-to-GDP differentials - are the main long-run drivers of sovereign spreads; (ii) liquidity risks and cumulated inflation differentials have non-negligible weights; but (iii) all conclusions are ultimately connected to whether or not the sample of countries is composed of members of an Optimal Currency Area (OCA). In particular, we establish (i) that results are overall driven by those countries not passing the OCA test; and (ii) that investors closely monitor and severely punish the deterioration of expected debt positions of those economies exhibiting significant gaps in competitiveness